Predicting Parameters for Audiological Complications in Pediatric Patients Affected by Meningitis - Bozzola, Elena; Spina, Giulia; Marsella, Pasquale; Scorpecci, Alessandro; Mascolo, Cristina; Salvatori, Martina; Roversi, Marco; Villani, Alberto (Journal of Pediatric Infectious Diseases, 2021)
Objective Meningitis is one of the most common causes of acquired sensorineural hearing loss in childhood. The aim of this study was to identify parameters predicting long-term audiological complications in meningitis.Methods Patients under 18 years admitted to the Bambino Gesù Pediatric Hospital between March 2001 and February 2019 with a diagnosis of meningitis entered the study. Audiological complications had been investigated during hospitalization and at follow-up.Results During the study period, 425 patients were enrolled. Sensorineural hearing loss was observed in 48 patients (11.3%). Multivariate analysis has shown that female gender predisposes to the development of permanent hearing loss after meningitis. Hearing impairment was associated with pneumococcal etiology (p < 0.001), lethargy (p = 0.027), reduced cerebrospinal fluid glucose level (26.18 mg/dL, p = 0.004), increase in both C-reactive protein (17.77 mg/dL, p = 0.001), and erythrocyte sedimentation rate (106.3 mm/h, p = 0.004). At follow-up, 19 patients had a persisting hearing damage, 7 recovered their hearing capacity and 20 were lost to follow-up. Among patients with permanent hearing damage, treatment was necessary in 16 patients. In details, 6 patients required external hearing aids and 10 patients required a cochlear implant.Conclusions Female gender, lethargy at onset, reduced cerebrospinal fluid glucose level, increased inflammation index, and pneumococcal etiology are correlated with sensorineural hearing damage in meningitis patients.
Keywords: meningitis; children; hearing loss/impairment; audiological sequelae